Multilayer silicon dioxide nanoparticle, preparation method thereof, antireflection film and solar cell

By simply centrifugal water washing on hollow-mesoporous silica nanoparticles, the problem of using template agent to remove complex and toxic solvents in the prior art is solved, and efficient and safe preparation of multi-layer silica nanoparticles is achieved, and its performance in anti-reflective film is improved.

CN120081382AActive Publication Date: 2025-06-03TRINA SOLAR CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510242722.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-06-03
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

In the prior art, when preparing hollow mesoporous silica nanoparticles, the template agent removal method is complicated, and toxic solvents are used, and it is easy to cause particle agglomeration and redispersion, which affects the light transmission effect of the anti-reflective film.

Method used

Multi-layer silica nanoparticles were prepared by a simple centrifugal washing method and a silica cladding layer was formed on its surface. The process is simple, with mild reaction conditions, high efficiency and no toxic solvents are used.

Benefits of technology

The efficient preparation of multi-layer silica nanoparticles is achieved, and the efficiency of detemplate agent reaches 100%, which improves the mechanical strength of the nanoparticles, makes them suitable for anti-reflective film materials and improves the light transmission effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120081382A_ABST
    Figure CN120081382A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solar cells, and discloses a multilayer silicon dioxide nanoparticle, a preparation method thereof, an antireflection film and a solar cell. The multilayer silicon dioxide nanoparticles comprise a hollow inner core, a silicon dioxide mesoporous middle layer and a silicon dioxide coating shell. The preparation method disclosed by the invention is simple, the reaction condition is mild and non-toxic, the efficiency is high, the template agent is thoroughly removed, and the synthesized multilayer silicon dioxide nanoparticles are high in porosity, good in light transmission effect, good in dispersity and relatively good in mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solar cells, and particularly relates to a multi-layer silicon dioxide nanoparticle, a preparation method thereof, an antireflection film, and a solar cell. Background Art

[0002] Due to their excellent mechanical strength and adjustable porosity, porous silicon dioxide nanoparticles are widely used in antireflection film materials. The sol-gel method for synthesizing porous silicon dioxide nanoparticles is simple and low-cost. Currently, the pore formation method of porous silicon dioxide in the sol-gel method is mostly the template method. First, a template agent is introduced into the silicon source system. The template agent is generally an organic polymer or an organic surfactant. During the hydrolysis of the silicon source into silicon dioxide sol, the template is coated inside the silicon particles to form bundles or spheres. After the silicon source is hydrolyzed, the template agent is removed. The removal methods of the template agent are mostly calcination or water washing. However, calcination will cause the organic matter to oxidize and turn black, leaving carbon black inside the silicon particles. During the water washing process, due to the relatively dense internal structure of the silicon oxide particles, it is difficult for the template agent to be completely soaked and dissolved by water. The effects of removing the template by both methods are not ideal enough, and the pores inside the silicon dioxide cannot be completely released, thereby affecting the light transmission effect of the antireflection film.

[0003] CN110217802B synthesizes an amphiphilic block copolymer pDMAEMA b pGMA and uses it as a template, enabling the amphiphilic block copolymer to self-assemble into nanostructures with controllable size and shape in an aqueous solution, providing good template molecules for controlling the growth of SiO 2 nanoparticles and the construction of uniform assemblies. Then, under room temperature conditions, hollow mesoporous silica functional microspheres are synthesized by a one-step method. The prepared hollow mesoporous silica functional microspheres have a large hollow inner cavity volume and controllable size.

[0004] CN117585681A uses tetraethyl orthosilicate (TEOS) as the silicon source, and polyethyleneimine (PEI) and cetyltrimethylammonium bromide (CTAB) as the structure-directing agents for the hollow structure of the silica microspheres and the mesoporous channels respectively. Hollow silica spheres are prepared by a one-step method, and finally, the template is completely removed by calcination in air to obtain hollow mesoporous silica spheres.

[0005] For the hollow mesoporous silica prepared by the prior art, the synthesis process of the template agent used is complex and cumbersome, the synthesis period is long, and toxic organic solvents such as tetrahydrofuran are used, which are harmful to the environment and the human body. Moreover, the template agent is removed by a calcination process, which easily causes particle aggregation and cannot be redispersed, and thus cannot be applied to antireflection film materials. Summary of the Invention

[0006] In view of the above problems existing in the prior art, the present invention provides a multi-layer silica nanoparticle, a preparation method thereof, an antireflection film and a solar cell. The template removing agent efficiency of the multi-layer silica nanoparticle of the present invention is almost 100%, and it has high mechanical strength and can be applied to antireflection film materials.

[0007] Specifically, one aspect of the present invention provides a multi-layer silica nanoparticle, which sequentially includes a hollow core, a mesoporous silica intermediate layer and a silica coating layer from the inside to the outside, and the overall porosity of the multi-layer silica nanoparticle is 25-50%.

[0008] In one or more embodiments, the particle size of the multi-layer silica nanoparticle is 80-120 nm.

[0009] In one or more embodiments, the thickness of the silica coating layer of the multi-layer silica nanoparticle is 5-8 nm.

[0010] In one or more embodiments, the thickness of the mesoporous silica intermediate layer of the multi-layer silica nanoparticle is 20-35 nm.

[0011] In one or more embodiments, the diameter of the hollow core of the multi-layer silica nanoparticle is 30-70 nm.

[0012] In one or more embodiments, the specific surface area of the multi-layer silica nanoparticle before coating the silica coating layer is 320-400 m 2 / g.

[0013] In one or more embodiments, the mesoporous pore diameter of the multi-layer silica nanoparticle before coating the silica coating layer is 10-20 nm.

[0014] In one or more embodiments, the porosity of the multi-layer silica nanoparticle before coating the silica coating layer is 30-55%.

[0015] In one or more embodiments, the multi-layer silica nanoparticle does not contain mesoporous pore-forming agents and hollow pore-forming agents.

[0016] Another aspect of the present invention provides a method for preparing the multi-layer silica nanoparticle according to any embodiment of the present invention. The preparation method includes: dispersing hollow silica nanoparticles in a mixed solvent of an alcohol solvent and water, adjusting the pH value of the solution to 7-14, adding a silicon source, and reacting to form a silica coating layer on the surface of the hollow silica nanoparticles to obtain the multi-layer silica nanoparticles; wherein, the hollow silica nanoparticles include a hollow core and a mesoporous silica shell.

[0017] In one or more embodiments, the particle size of the hollow silica nanoparticles is 70 nm - 110 nm.

[0018] In one or more embodiments, the diameter of the hollow core of the hollow silica nanoparticles is 30 - 70 nm.

[0019] In one or more embodiments, the thickness of the mesoporous silica shell of the hollow silica nanoparticles is 20 - 35 nm.

[0020] In one or more embodiments, the specific surface area of the hollow silica nanoparticles is 320 - 400 m 2 / g.

[0021] In one or more embodiments, the mesopore diameter of the hollow silica nanoparticles is 10 - 20 nm.

[0022] In one or more embodiments, the porosity of the hollow silica nanoparticles is 30 - 55%.

[0023] In one or more embodiments, the alcohol solvent is selected from C1 - C4 alcohols.

[0024] In one or more embodiments, the alcohol solvent is ethanol.

[0025] In one or more embodiments, the volume ratio of the alcohol solvent to water in the mixed solvent is (5 - 10):1.

[0026] In one or more embodiments, the silicon source is tetraethyl orthosilicate.

[0027] In one or more embodiments, the mass ratio of the silicon source to the hollow silica nanoparticles is 1:(0.3 - 1).

[0028] In one or more embodiments, the reaction temperature is 20 - 30 °C.

[0029] In one or more embodiments, the reaction time is 5 - 8 h.

[0030] In one or more embodiments, ammonia water is used to adjust the pH value of the solution to 7 - 14.

[0031] In one or more embodiments, the method for preparing the hollow silica nanoparticles includes:

[0032] S1: Dissolve a hollow pore former, a mesoporous pore former, an initiator, and a silicon source in a solvent, and react at 5 - 10 °C to obtain a solution containing nanoparticles P 0 of the solution, the nanoparticles P 0It includes a hollow pore-forming agent core and a silica surface layer, and the silica surface layer contains mesoporous channels and mesoporous pore-forming agents filled in the mesoporous channels;

[0033] S2: Remove the nanoparticle P by centrifugal washing with water 0 from the mesoporous pore-forming agent in the mesoporous channels of, to obtain nanoparticle P 1 ;

[0034] S3: Disperse the nanoparticle P 1 in water, adjust the pH value of the solution to 1 - 1.5, then stir at 60 - 70 °C, and remove the hollow pore-forming agent by centrifugal washing with water to obtain the hollow silica nanoparticles.

[0035] In one or more embodiments, in step S1, the hollow pore-forming agent is polyacrylic acid, and the relative molecular weight of polyacrylic acid is preferably 3000 - 5000.

[0036] In one or more embodiments, in step S1, the mesoporous pore-forming agent is cetyltrimethylammonium bromide and / or cetyltrimethylammonium chloride.

[0037] In one or more embodiments, in step S1, the initiator is ammonia water.

[0038] In one or more embodiments, in step S1, the silicon source is tetraethyl orthosilicate.

[0039] In one or more embodiments, in step S1, the solvent is a mixture of an alcohol solvent and water.

[0040] In one or more embodiments, in step S1, the alcohol solvent is a C1 - C4 alcohol.

[0041] In one or more embodiments, in step S1, the alcohol solvent is ethanol.

[0042] In one or more embodiments, in step S1, the nanoparticle P 0 has a particle size of 70 - 110 nm.

[0043] In one or more embodiments, in step S1, the mass ratio of the hollow pore-forming agent, the mesoporous pore-forming agent and the silicon source is 1:(0.5 - 1.5):(15 - 40).

[0044] In one or more embodiments, in step S1, the reaction time is 5 - 8 h.

[0045] In one or more embodiments, step S1 includes the following steps:

[0046] S1-1: Mix the hollow pore former, initiator and water evenly, then add them to an alcohol solvent and stir evenly to obtain a first mixed solution.

[0047] S1-2: Dissolve the mesoporous pore former in water, then add it to the first mixed solution prepared in step S1-1 to obtain a second mixed solution.

[0048] S1-3: Add the silicon source to the second mixed solution and react at 5 - 10 °C to obtain the solution containing nanoparticle P 0 .

[0049] In one or more embodiments, in step S2, the water used for centrifugal washing is ice water with a temperature of 0 - 5 °C.

[0050] In one or more embodiments, in step S3, the stirring time is greater than or equal to 10 h.

[0051] In one or more embodiments, in step S3, the stirring time is 10 - 12 h.

[0052] Another aspect of the present invention provides a multi-layered silica nanoparticle prepared by the method of any one of the embodiments herein.

[0053] Another aspect of the present invention provides an antireflection film, which comprises the multi-layered silica nanoparticles prepared by any one of the embodiments herein.

[0054] Another aspect of the present invention provides a solar cell, which comprises the antireflection film prepared by any one of the embodiments herein.

[0055] The present invention has the following beneficial technical effects: The synthesis process of the present invention is simple, the reaction conditions are mild, and the efficiency is high. The template agent of the hollow-mesoporous silica nanoparticles can be completely removed by simple centrifugal washing; after removing the template, a silica shell layer structure is coated on the surface of the hollow-mesoporous silica nanoparticles, so that the synthesized multi-layered silica nanoparticles have good mechanical strength and can be used for the preparation of the antireflection film coating in solar cells. Description of the Drawings

[0056] Figure 1 It is a schematic structural diagram of the multi-layered silica nanoparticles of the present invention. Detailed Embodiments

[0057] To enable those skilled in the art to understand the features and effects of the present invention, the following provides a general description and definition of the terms and expressions mentioned in this text. Unless otherwise specified, all technical and scientific terms used in the text shall have the ordinary meanings understood by those skilled in the art regarding the present invention. In case of conflicts, the definitions in this specification shall prevail.

[0058] The theories or mechanisms described and disclosed in this text, whether correct or incorrect, shall not limit the scope of the present invention in any way, that is, the content of the present invention can be implemented without being restricted by any specific theory or mechanism.

[0059] In this text, "comprising", "including", "containing" and similar expressions cover the meanings of "consisting essentially of" and "consisting of". For example, when it is disclosed in this text that "A comprises B and C", "A consists essentially of B and C" and "A consists of B and C" should be considered as having been disclosed in this text.

[0060] In this text, all features defined in the form of numerical ranges or percentage ranges, such as numerical values, quantities, contents and concentrations, are only for the sake of brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be regarded as having covered and specifically disclosed all possible sub-ranges and individual numerical values within the ranges (including integers and fractions).

[0061] In this text, unless otherwise specified, percentages refer to mass percentages and ratios refer to mass ratios.

[0062] In this text, when describing embodiments or examples, it should be understood that it is not used to limit the present invention to these embodiments or examples. On the contrary, all alternatives, improvements and equivalents of the methods and materials described in the present invention can be covered within the scope defined by the present invention.

[0063] In this text, for the sake of concise description, all possible combinations of all technical features in each embodiment or example are not described. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each embodiment or example can be combined arbitrarily, and all possible combinations should be considered as being within the scope described in this specification.

[0064] The present invention achieves the effect of thoroughly removing the template agent of hollow-mesoporous silica nanoparticles through simple centrifugation and water washing. After removing the template, a silica shell structure is coated on the surface of the hollow-mesoporous silica nanoparticles to enhance the mechanical strength of the nanoparticles, so that the multi-layer silica nanoparticles in the present invention can be applied to antireflection film materials.

[0065] The multi-layer silica nanoparticles of the present invention can be prepared by a method comprising the following steps:

[0066] S1: Using polyacrylic acid (PAA) as the hollow pore former, cetyltrimethylammonium bromide (CTAB) or cetyltrimethylammonium chloride (CTAC) as the mesoporous pore former, ammonia water as the initiator, tetraethyl orthosilicate as the silicon source, and ethanol and water as the solvents, react at 5 - 10 °C to obtain a solution containing nanoparticles P 0 The nanoparticles P 0 contain a polyacrylic acid core and a silica surface layer, and the silica surface layer contains mesoporous channels and mesoporous pore formers filled in the mesoporous channels;

[0067] S2: Treat the solution containing nanoparticles P 0 obtained in step S1 by centrifugation and washing with water to remove the mesoporous pore formers in the mesoporous channels, and then remove the solvents to obtain nanoparticles P 1 ;

[0068] S3: Disperse the nanoparticles P 1 obtained in step S2 in water, adjust the pH value of the solution to 1 - 1.5 by adding acid, then stir at 60 - 70 °C, and use centrifugation and washing with water to remove polyacrylic acid to obtain nanoparticles P 2 ;

[0069] S4: Disperse the nanoparticles P 2 obtained in step S3 in a mixed solvent of ethanol and water, add ammonia water to adjust the pH value of the solution to 7 - 14, then add tetraethyl orthosilicate and carry out the reaction to form a silica coating layer on the surface of the nanoparticles P 2 to obtain multi-layer silica nanoparticles.

[0070] In the present invention, the water is preferably deionized water.

[0071] In step S1 of the present invention, the particle size of the nanoparticles P 0 is preferably 70 - 110 nm, such as 71 nm, 72 nm, 73 nm, 74 nm, 75 nm, 76 nm, 77 nm, 78 nm, 79 nm, 80 nm, 81 nm, 82 nm, 83 nm, 84 nm, 85 nm, 86 nm, 87 nm, 88 nm, 89 nm, 90 nm, 91 nm, 92 nm, 93 nm, 94 nm, 95 nm, 96 nm, 97 nm, 98 nm, 99 nm, 100 nm, 101 nm, 102 nm, 103 nm, 104 nm, 105 nm, 106 nm, 107 nm, 108 nm, 109 nm.

[0072] In step S1 of the present invention, the relative molecular weight of the polyacrylic acid can be 3000 - 5000, such as 3500, 4000, 4500.

[0073] In step S1 of the present invention, the mass ratio of the hollow pore former to the mesoporous pore former is preferably 1:(0.5 - 1.5), such as 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4.

[0074] In step S1 of the present invention, the mass ratio of the hollow pore former to tetraethyl orthosilicate is preferably 1:(15 - 40), such as 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29, 1:30, 1:31, 1:32, 1:33, 1:34, 1:35, 1:36, 1:37, 1:38, 1:39.

[0075] In step S1 of the present invention, the reaction temperature is preferably 5 - 10°C, such as 6°C, 7°C, 8°C, 9°C. The present invention controls the reaction in step S1 to be carried out in a low-temperature system, which is beneficial to the formation of a mesoporous structure with large pore diameters, and thus is beneficial to the dissolution of the hollow pore former PAA.

[0076] In step S2 of the present invention, the water used for high-speed centrifugation is preferably ice water with a temperature of 0 - 5°C, such as 0°C, 1°C, 2°C, 3°C, 4°C, 5°C. Due to the presence of the surfactant, it will increase the surface activity of the silica nanoparticles, accelerate the gelation rate between the particles and thus cause agglomeration. Using ice water with a temperature below 5°C in step S2 of the present invention can effectively prevent the agglomeration of nanoparticles.

[0077] In step S3 of the present invention, the acid used is a common Lewis acid, such as hydrochloric acid. In step S3 of the present invention, by adding acid to adjust the pH value of the solution to 1 - 1.5 and heating and stirring in a strong acidic system, it is beneficial to accelerate the dissolution of the hollow pore former PAA and achieve the effect of completely removing the pore former template.

[0078] In step S3 of the present invention, controlling the stirring temperature to be 60 - 70°C is beneficial to the full removal of polyacrylic acid and achieve the effect of completely removing the hollow pore former.

[0079] In step S4 of the present invention, the volume ratio of ethanol to water in the mixed solvent can be (5 - 10):1, such as 6:1, 7:1, 8:1, 9:1.

[0080] In step S4 of the present invention, the mass ratio of tetraethyl orthosilicate to nanoparticle P 2 can be 1:(0.3 - 1), such as 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9.

[0081] In step S4 of the present invention, the reaction temperature can be 20 - 30 °C, such as 21 °C, 22 °C, 23 °C, 24 °C, 25 °C, 26 °C, 27 °C, 28 °C, 29 °C.

[0082] In step S4 of the present invention, the thickness of the silica shell layer is preferably 5 - 8 nm, such as 6 nm, 7 nm. The silica shell layer coated on the surface of the multi-layer silica nanoparticles of the present invention is beneficial to improving the mechanical strength of the nanoparticles. In the present invention, the shell layer is silica, which means that no pore-forming agent is added in the reaction for preparing the silica shell layer. Therefore, the silica shell layer has higher properties compared to the silica intermediate layer. The present invention preferably controls the thickness of the silica shell layer within 5 - 8 nm. On the one hand, it can improve the mechanical strength of the nanoparticles and the antireflection film. On the other hand, it will not cause excessive decrease in the light transmittance of the silica nanoparticles.

[0083] In some embodiments, the multi-layer silica nanoparticles with a silica shell layer coated on the surface are prepared according to the following steps:

[0084] S1: Take 0.025 - 0.5 g of PAA with a relative molecular weight of 5000, 1 mL of ammonia water with a mass fraction of 25 wt%, and 5 mL of deionized water. After mixing and stirring evenly, add them to 100 mL of anhydrous ethanol under high-speed magnetic stirring to obtain a first solution; weigh 0.3 - 0.6 g of CTAB and dissolve it in 5 mL of deionized water. After fully stirring and dissolving, add it to the above first solution. After mixing and stirring evenly, a second solution is obtained; finally, add 5 - 10 mL of TEOS to the second solution, and use a cold water bath to control the reaction temperature of the mixed solution at 5 - 10 °C, and continuously stir for 5 - 8 h to obtain nanoparticles P with a particle size of 70 - 110 nm and containing PAA and CTAB 0 ;

[0085] S2: Wash the nanoparticles P obtained in step S1 with ice deionized water at a temperature lower than 5 °C 0 , and wash away the mesoporous pore-forming agent CTAB by centrifugation to obtain nanoparticles P containing PAA 1 ;

[0086] S3: Redisperse the nanoparticles P obtained in step S2 1 in deionized water, add hydrochloric acid to adjust the pH value of the solution to 1 - 1.5, heat it in a water bath to 60 - 70 °C, stir for 10 - 12 h, then centrifuge and wash with water to obtain template-free nanoparticles P without PAA 2 ;

[0087] S4: The nanoparticles P obtained in step S3 2Redisperse in a mixed solution of 100 ml of absolute ethanol and 10 ml of deionized water, add 0.5 - 1 ml of ammonia water and 5 - 8 ml of TEOS, stir at room temperature for 5 - 8 h, and finally obtain multi-layer silica nanoparticles with a silica shell layer on the surface. Among them, the thickness of the silica shell layer is 5 - 8 nm, and the particle size of the multi-layer silica nanoparticles is 80 - 120 nm.

[0088] The multi-layer silica nanoparticles prepared by the method of the present invention can completely remove the template agent, and the template agent can be a mesoporous pore-forming agent, a hollow pore-forming agent or a template agent with other functions.

[0089] The particle size of the multi-layer silica nanoparticles of the present invention can be 80 - 120 nm, such as 81 nm, 82 nm, 83 nm, 84 nm, 85 nm, 86 nm, 87 nm, 88 nm, 89 nm, 90 nm, 91 nm, 92 nm, 93 nm, 94 nm, 95 nm, 96 nm, 97 nm, 98 nm, 99 nm, 100 nm, 101 nm, 102 nm, 103 nm, 104 nm, 105 nm, 106 nm, 107 nm, 108 nm, 109 nm, 110 nm, 111 nm, 112 nm, 113 nm, 114 nm, 115 nm, 116 nm, 117 nm, 118 nm, 119 nm, 120 nm.

[0090] The thickness of the mesoporous silica intermediate layer of the multi-layer silica nanoparticles of the present invention can be 20 - 35 nm, such as 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, 31 nm, 32 nm, 33 nm, 34 nm.

[0091] The diameter of the hollow core of the multi-layer silica nanoparticles of the present invention can be 30 - 70 nm, such as 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm.

[0092] The specific surface area of the multi-layer silica nanoparticles of the present invention before coating the silica coating layer can be 320 - 400 m 2 / g, such as 330 m 2 / g, 340 m 2 / g, 350 m 2 / g, 360 m 2 / g, 370 m 2 / g, 380 m 2 / g, 390 m 2 / g.

[0093] Before coating the silica coating layer, the mesopore diameter of the multi-layer silica nanoparticles of the present invention can be 10-20 nm, such as 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm.

[0094] The porosity of the multi-layer silica nanoparticles of the present invention can be 25-50%, such as 30%, 35%, 40%, 45%.

[0095] Before coating the silica coating layer, the porosity of the multi-layer silica nanoparticles of the present invention can be 30-55%, such as 35%, 40%, 45%, 50%.

[0096] The antireflection film of the present invention comprises the multi-layer silica nanoparticles described in any one of the embodiments herein. The antireflection film of the present invention can be prepared by coating and drying a coating solution comprising the multi-layer silica nanoparticles described in any one of the embodiments herein. In the present invention, the coating solution comprises the multi-layer silica nanoparticles of the present invention, a solvent and a crosslinking agent. The solvent can be a mixture of water and ethanol, and the crosslinking agent can be small particle silica nanoparticles obtained by acid-catalyzed hydrolysis of TEOS.

[0097] The present invention will be illustrated below by way of specific examples. It should be understood that these examples are illustrative only and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are conventional methods, reagents and materials in the art unless otherwise specified. The compounds in the examples can be obtained through commercial channels.

[0098] In the present invention, SiO 2 The particle size of the nanoparticles was measured by a laser nanoparticle size analyzer.

[0099] In the present invention, the thickness of the silica coating layer, the thickness of the mesoporous silica intermediate layer and the diameter of the hollow core were observed and photographed by transmission electron microscopy (TEM), and the actual sizes were measured according to the photographing ratio of the photos, and then obtained by calculation.

[0100] In the present invention, the specific surface area, mesopore diameter and particle porosity of the silica nanoparticles were measured by a specific surface area analyzer.

[0101] In the present invention, the method for preparing the crosslinking agent of the antireflection coating solution is as follows: Dissolve 0.1 g of concentrated hydrochloric acid with a mass fraction of 36 wt% in a mixed solution of 100 g of deionized water and absolute ethanol (the mass ratio of deionized water to absolute ethanol is 1:5). After mixing evenly, add 20 mL of TEOS at one time, and magnetically stir at room temperature for 5-8 h to obtain the crosslinking agent of the antireflection coating solution.

[0102] Example 1

[0103] In this embodiment, the silica-coated multi-layer silica nanoparticles P are prepared through the following steps:

[0104] S1: Take 0.5 g of PAA with a relative molecular weight of 5000, 1 mL of ammonia water with a mass fraction of 25 wt%, and 5 mL of deionized water. After mixing and stirring evenly, add them to 100 mL of anhydrous ethanol under high-speed magnetic stirring to obtain a first solution; weigh 0.4 g of CTAB and dissolve it in 5 mL of deionized water. After sufficient stirring and dissolution, add it to the above first solution. After mixing and stirring evenly, a second solution is obtained; finally, add 8 mL of TEOS to the second solution, and use a cold water bath to control the reaction temperature of the mixed solution at 5 - 10 °C, and continuously stir for 6 h to obtain nanoparticles P containing PAA and CTAB 0 , with a particle size of 100 - 110 nm;

[0105] S2: Wash the nanoparticles P obtained in step S1 with ice deionized water at a temperature lower than 5 °C 0 , and remove the mesoporous pore-forming agent CTAB by centrifugation to obtain nanoparticles P containing PAA 1 ;

[0106] S3: Redisperse the nanoparticles P obtained in step S2 1 in deionized water, add hydrochloric acid to adjust the pH value of the solution to 1.5, heat it in a water bath to 65 °C, stir for 10 h, then centrifuge and wash with water to obtain template-free nanoparticles P without PAA 2 ;

[0107] S4: Redisperse the nanoparticles P obtained in step S3 2 in a mixed solution of 100 ml of anhydrous ethanol and 10 ml of deionized water, add 0.75 ml of ammonia water and 7 ml of TEOS, stir at room temperature for 6 h, and finally obtain multi-layer silica nanoparticles P with a silica shell layer on the surface. Among them, the diameter of the hollow core is 60 - 70 nm, the thickness of the mesoporous silica intermediate layer is 20 - 25 nm, the thickness of the silica shell layer is 5 - 8 nm, and the particle size of the multi-layer silica nanoparticles P is 110 - 120 nm.

[0108] Example 2

[0109] In this example, steps S1 - S4 in Example 1 are repeated to prepare the silica-coated multi-layer silica nanoparticles P, but the difference is that: the stirring duration in step S3 is 20 h.

[0110] Example 3

[0111] In this embodiment, the silica-coated multi-layer silica nanoparticles P are prepared through the following steps:

[0112] S1: Take 0.25 g of PAA with a relative molecular weight of 5000, 1 mL of ammonia water with a mass fraction of 25 wt%, and 5 mL of deionized water. After mixing and stirring evenly, add them to 100 mL of anhydrous ethanol under high-speed magnetic stirring to obtain a first solution; weigh 0.3 g of CTAB and dissolve it in 5 mL of deionized water. After fully stirring and dissolving, add it to the above first solution. After mixing and stirring evenly, a second solution is obtained; finally, add 10 mL of TEOS to the second solution, and use a cold water bath to control the reaction temperature of the mixed solution at 5 - 10 °C, and continuously stir for 6 h to obtain nanoparticles P containing PAA and CTAB 0 , with a particle size of 90 - 100 nm;

[0113] S2: Wash the nanoparticles P obtained in step S1 with ice deionized water with a temperature below 5 °C 0 , and wash away the mesoporous pore-forming agent CTAB by centrifugation to obtain nanoparticles P containing PAA 1 ;

[0114] S3: Redisperse the nanoparticles P obtained in step S2 1 in deionized water, add hydrochloric acid to adjust the pH value of the solution to 1.5, heat it in a water bath to 65 °C, stir for 10 h, then centrifuge and wash with water to obtain template-free nanoparticles P without PAA 2 ;

[0115] S4: Redisperse the nanoparticles P obtained in step S3 2 in a mixed solution of 100 ml of anhydrous ethanol and 10 ml of deionized water, add 0.75 ml of ammonia water and 6 ml of TEOS, stir at room temperature for 6 h, and finally obtain multi-layer silica nanoparticles P with a silica shell layer on the surface. Among them, the diameter of the hollow core is 30 - 40 nm, the thickness of the mesoporous silica middle layer is 30 - 35 nm, the thickness of the silica shell layer is 5 - 8 nm, and the particle size of the multi-layer silica nanoparticles P is 100 - 110 nm.

[0116] Example 4

[0117] The multi-layer silica nanoparticles P coated with silica are prepared in the following steps in this example:

[0118] S1: Take 0.5 g of PAA with a relative molecular weight of 5000, 1 mL of ammonia water with a mass fraction of 25 wt%, and 5 mL of deionized water. After mixing and stirring evenly, add them to 100 mL of anhydrous ethanol under high-speed magnetic stirring to obtain the first solution; weigh 0.6 g of CTAB and dissolve it in 5 mL of deionized water. After fully stirring and dissolving, add it to the above first solution. After mixing and stirring evenly, obtain the second solution; finally, add 8 mL of TEOS to the second solution, and use a cold water bath to control the reaction temperature of the mixed solution at 5 - 10 °C, and continuously stir for 6 h to obtain nanoparticles P containing PAA and CTAB 0 , with a particle size of 100 - 110 nm;

[0119] S2: Wash the nanoparticles P obtained in step S1 with ice deionized water with a temperature lower than 5 °C 0 , and wash away the mesoporous pore-forming agent CTAB by centrifugation to obtain nanoparticles P containing PAA 1 ;

[0120] S3: Redisperse the nanoparticles P obtained in step S2 1 in deionized water, add hydrochloric acid to adjust the pH value of the solution to 1.5, heat it in a water bath to 65 °C, stir for 10 h, then centrifuge and wash with water to obtain template-free nanoparticles P without PAA 2 ;

[0121] S4: Redisperse the nanoparticles P obtained in step S3 2 in a mixed solution of 100 ml of anhydrous ethanol and 10 ml of deionized water, add 0.75 ml of ammonia water and 7 ml of TEOS, stir at room temperature for 6 h, and finally obtain multi-layer silica nanoparticles P with a silica shell layer on the surface. Among them, the diameter of the hollow core is 60 - 70 nm, the thickness of the mesoporous silica middle layer is 20 - 25 nm, the thickness of the silica shell layer is 5 - 8 nm, and the particle size of the multi-layer silica nanoparticles P is 110 - 120 nm.

[0122] Example 5

[0123] The multi-layer silica nanoparticles P coated with silica are prepared in the following steps in this example:

[0124] S1: Take 0.25 g of PAA with a relative molecular weight of 5000, 1 mL of ammonia water with a mass fraction of 25 wt%, and 5 mL of deionized water. After mixing and stirring evenly, add them to 100 mL of anhydrous ethanol under high-speed magnetic stirring to obtain the first solution; weigh 0.3 g of CTAB and dissolve it in 5 mL of deionized water. After fully stirring and dissolving, add it to the above first solution. After mixing and stirring evenly, obtain the second solution; finally, add 5 mL of TEOS to the second solution, and use a cold water bath to control the reaction temperature of the mixed solution at 5 - 10 °C, and continuously stir for 6 h to obtain nanoparticles P containing PAA and CTAB 0 , with a particle size of 70 - 90 nm;

[0125] S2: Wash the nanoparticles P obtained in step S1 with ice deionized water at a temperature lower than 5 °C 0 , and remove the mesoporous pore-forming agent CTAB by centrifugation to obtain nanoparticles P containing PAA 1 ;

[0126] S3: Redisperse the nanoparticles P obtained in step S2 1 in deionized water, add hydrochloric acid to adjust the pH value of the solution to 1.5, heat it in a water bath to 65 °C, stir for 10 h, then centrifuge and wash with water to obtain template-free nanoparticles P without PAA 2 ;

[0127] S4: Redisperse the nanoparticles P obtained in step S3 2 in a mixed solution of 100 ml of anhydrous ethanol and 10 ml of deionized water, add 0.75 ml of ammonia water and 5 ml of TEOS, stir at room temperature for 6 h, and finally obtain multi-layer silica nanoparticles P with a silica shell layer on the surface. Among them, the diameter of the hollow core is 30 - 40 nm, the thickness of the mesoporous silica middle layer is 20 - 25 nm, the thickness of the silica shell layer is 5 - 8 nm, and the particle size of the multi-layer silica nanoparticles P is 80 - 100 nm.

[0128] Comparative Example 1

[0129] In this example, multi-layer silica nanoparticles P coated with silica are prepared through the following steps:

[0130] S1: Take 0.5 g of PAA with a relative molecular weight of 5000, 1 mL of ammonia water with a mass fraction of 25 wt%, and 5 mL of deionized water. After mixing and stirring evenly, add them to 100 mL of anhydrous ethanol under high-speed magnetic stirring to obtain a first solution; weigh 0.4 g of CTAB and dissolve it in 5 mL of deionized water. After sufficient stirring and dissolution, add it to the above first solution. After mixing and stirring evenly, a second solution is obtained; finally, add 8 mL of TEOS to the second solution, and use a cold water bath to control the reaction temperature of the mixed solution at 25 °C, and continuously stir for 6 h to obtain nanoparticles P containing PAA and CTAB 0 ;

[0131] S2: Wash the nanoparticles P obtained in step S1 with ice deionized water at a temperature lower than 5 °C 0 , and remove the mesoporous pore-forming agent CTAB by centrifugation to obtain nanoparticles P containing PAA 1 ;

[0132] S3: Redisperse the nanoparticles P obtained in step S2 1 in deionized water, add hydrochloric acid to adjust the pH value of the solution to 1.5, heat it in a water bath to 65 °C, stir for 10 h, then centrifuge and wash with water to obtain template-free nanoparticles P without PAA 2 ;

[0133] S4: Redisperse the nanoparticles P obtained in step S3 2 in a mixed solution of 100 ml of anhydrous ethanol and 10 ml of deionized water, add 0.75 ml of ammonia water and 7 ml of TEOS, stir at room temperature for 6 h, and finally obtain multi-layer silica nanoparticles P with a silica shell layer on the surface. Among them, the diameter of the hollow core is 60 - 70 nm, the thickness of the mesoporous silica middle layer is 20 - 25 nm, the thickness of the silica shell layer is 5 - 8 nm, and the particle size of the multi-layer silica nanoparticles P is 110 - 120 nmnm

[0134] Comparative Example 2

[0135] This example prepares multi-layer silica nanoparticles P coated with silica through the following steps:

[0136] S1: Take 0.5 g of PAA with a relative molecular weight of 5000, 1 mL of ammonia water with a mass fraction of 25 wt%, and 5 mL of deionized water. After mixing and stirring evenly, add them to 100 mL of anhydrous ethanol under high-speed magnetic stirring to obtain a first solution; weigh 0.4 g of CTAB and dissolve it in 5 mL of deionized water. After fully stirring and dissolving, add it to the above first solution. After mixing and stirring evenly, a second solution is obtained; finally, add 8 mL of TEOS to the second solution, and use a cold water bath to control the reaction temperature of the mixed solution at 5 - 10 °C, and continuously stir for 6 h to obtain nanoparticles P containing PAA and CTAB 0 ;

[0137] S2: Wash the nanoparticles P obtained in step S1 with ice deionized water with a temperature below 5 °C 0 , and remove the mesoporous pore-forming agent CTAB by centrifugation to obtain nanoparticles P containing PAA 1 ;

[0138] S3: Redisperse the nanoparticles P obtained in step S2 1 in deionized water, add hydrochloric acid to adjust the pH value of the solution to 7, heat it in a water bath to 65 °C, stir for 10 h, then centrifuge and wash with water to obtain template-free nanoparticles P without PAA 2 ;

[0139] S4: Redisperse the nanoparticles P obtained in step S3 2 in a mixed solution of 100 ml of anhydrous ethanol and 10 ml of deionized water, add 0.75 ml of ammonia water and 7 ml of TEOS, stir at room temperature for 6 h, and finally obtain multi-layer silica nanoparticles P with a silica shell layer on the surface. Among them, the diameter of the hollow core is 60 - 70 nm, the thickness of the mesoporous silica middle layer is 20 - 25 nm, the thickness of the silica shell layer is 5 - 8 nm, and the particle size of the multi-layer silica nanoparticles P is 110 - 120 nm.

[0140] Comparative Example 3

[0141] This example prepares multi-layer silica nanoparticles P coated with silica through the following steps:

[0142] S1: Take 0.5 g of PAA with a relative molecular weight of 5000, 1 mL of ammonia water with a mass fraction of 25 wt%, and 5 mL of deionized water. After mixing and stirring evenly, add them to 100 mL of anhydrous ethanol under high-speed magnetic stirring to obtain a first solution; weigh 0.4 g of CTAB and dissolve it in 5 mL of deionized water. After fully stirring and dissolving, add it to the above first solution. After mixing and stirring evenly, a second solution is obtained; finally, add 8 mL of TEOS to the second solution, and use a cold water bath to control the reaction temperature of the mixed solution at 5 - 10 °C, and continuously stir for 6 h to obtain nanoparticles P containing PAA and CTAB 0 ;

[0143] S2: Wash the nanoparticles P obtained in step S1 with ice deionized water at a temperature lower than 5 °C 0 , and remove the mesoporous pore-forming agent CTAB by centrifugation to obtain nanoparticles P containing PAA 1 ;

[0144] S3: Redisperse the nanoparticles P obtained in step S2 1 in deionized water, add hydrochloric acid to adjust the pH value of the solution to 1.5, stir at 25 °C for 10 h, then centrifuge and wash with water to obtain template-free nanoparticles P without PAA 2 ;

[0145] S4: Redisperse the nanoparticles P obtained in step S3 2 in a mixed solution of 100 ml of anhydrous ethanol and 10 ml of deionized water, add 0.75 ml of ammonia water and 7 ml of TEOS, stir at room temperature for 6 h, and finally obtain multi-layer silica nanoparticles P with a silica shell layer on the surface. Among them, the diameter of the hollow core is 60 - 70 nm, the thickness of the mesoporous silica middle layer is 20 - 25 nm, the thickness of the silica shell layer is 5 - 8 nm, and the particle size of the multi-layer silica nanoparticles P is 110 - 120 nm

[0146] Comparative Example 4

[0147] This example prepares silica nanoparticles P through the following steps 2 :

[0148] S1: Take 0.5 g of PAA with a relative molecular weight of 5000, 1 mL of ammonia water with a mass fraction of 25 wt%, and 5 mL of deionized water. After mixing and stirring evenly, add them to 100 mL of anhydrous ethanol under high-speed magnetic stirring to obtain the first solution; weigh 0.4 g of CTAB and dissolve it in 5 mL of deionized water. After fully stirring and dissolving, add it to the above first solution. After mixing and stirring evenly, obtain the second solution; finally, add 8 mL of TEOS to the second solution, and use a cold water bath to control the reaction temperature of the mixed solution at 25 °C, and continuously stir for 6 h to obtain nanoparticles P containing PAA and CTAB 0 ;

[0149] S2: Wash the nanoparticles P obtained in step S1 with ice deionized water at a temperature lower than 5 °C 0 , and remove the mesoporous pore-forming agent CTAB by centrifugation to obtain nanoparticles P containing PAA 1 ;

[0150] S3: Redisperse the nanoparticles P obtained in step S2 1 in deionized water, add hydrochloric acid to adjust the pH value of the solution to 1.5, heat it in a water bath to 65 °C, stir for 10 h, then centrifuge and wash with water to obtain template-free and silica shell-free silica nanoparticles P after removing PAA 2 .

[0151] Application Examples 1 - 5

[0152] Centrifuge and separate the multilayer silica nanoparticles P of Examples 1 - 2, Comparative Examples 1 - 3 and the nanoparticles P of Comparative Example 4 2 and add them to a mixed solvent with a mass ratio of anhydrous ethanol to deionized water of 9 / 1 respectively to obtain a solution, and the mass ratio of nanoparticles to solvent in the solution is 1 / 20; mix the solution with a cross-linking agent at a mass ratio of 1 / 2, and adjust the pH value of the mixed solution to 2.5 by dropping 1 mol / L hydrochloric acid solution and 1 mol / L ammonia water solution to obtain a coating solution

[0153] Coat the coating solution on the surface of float glass by a roll coating process. After drying, form an antireflection film with a thickness of 110 - 113 nm

[0154] Test Example 1

[0155] Use a transmission electron microscope to observe the structure of the nanoparticles, calculate the particle size of the hollow core and the thickness of the coating layer, and use a laser nanometer particle size analyzer to test the particle size of nanoparticles P before coating 2 and the particle size of nanoparticles P after coating, and use a specific surface area analyzer to measure nanoparticles P before coating 2The pore size of the mesoporous layer, the porosity and specific surface area of ​​the particles, and the porosity of the coated nanoparticles P, the preparation conditions of the nanoparticles are shown in Table 1, and the test results are shown in Table 2

[0156] Table 1: Examples 1-5, Comparative Examples 1-4 Nanoparticle P 2 Preparation conditions of nanoparticles P

[0157]

[0158] Table 2: Nanoparticle P of Examples 1-5 and Comparative Examples 1-4 2 Characterization test results of nanoparticles P

[0159]

[0160] As shown in Table 2, compared with Example 1, the time for removing the template agent (hollow pore-forming agent) in step S3 of Example 2 is doubled, while the porosity of the prepared multilayer silica nanoparticles P remains unchanged at about 52%, indicating that the template agent can be completely removed by the preparation method in Example 1. The difference between Example 1 and Comparative Example 1 is that the synthesized nanoparticles P in step S1 0 The reaction temperature is different. The mesopore diameter of the nanoparticles of Comparative Example 1 obtained by reacting at room temperature is significantly smaller than the mesopore diameter of the nanoparticles of Example 1 obtained by reacting at low temperature. This is because the low temperature environment of Example 1 will cause the micelle formation rate of CTAB to slow down, but the orderliness of the formed micelles is improved and the micelles are larger, so that the mesopore diameter of the synthesized nanoparticles is larger, and the large pore diameter is conducive to the dissolution of CTAB and PAA during the water washing process, while the nanoparticles synthesized in Comparative Example 1 have a small mesopore diameter, which is not conducive to the dissolution of CTAB and PAA, and the pore-forming agent cannot be completely removed, resulting in a small porosity of the nanoparticles. Comparing Example 1 and Example 3, the amount of PAA added in Example 3 is reduced, and the amount of TEOS added is increased, which makes the hollow core smaller and the thickness of the mesoporous layer thicker. At the same time, due to the reduction in the amount of CTAB added, the mesopore diameter of the synthesized particles becomes smaller, and the porosity of the nanoparticles decreases; Comparing Example 1 and Example 4, the amount of CTAB added is increased, so that the mesopore diameter of the synthesized nanoparticles increases; Comparing Example 3 and Example 5, the amount of TEOS added is reduced, so that the thickness of the mesoporous layer of the synthesized nanoparticles becomes thinner, the particle size of the nanoparticles decreases, and the porosity increases.

[0161] The difference between Example 1 and Comparative Example 2 lies in the pH value in Step S3. In Example 1, the pH value was adjusted to 1.5 during the removal of PAA. The strong acid system will accelerate the dissolution of PAA. This is because during the particle synthesis process, after ammonia water was added to the system, PAA was ammoniated and showed a positive charge in the system, while the silica sol hydrolyzed from TEOS showed a negative charge. The attraction between positive and negative charges made it difficult for PAA to detach from the silica shell. When a strong acid was added to the solution, acid-base neutralization caused PAA to become carboxylated again and show a negative charge, accelerating the dissolution rate of PAA and making it easy to achieve complete release of the porosity of the nanoparticles.

[0162] The difference between the example and Comparative Example 3 lies in the temperature in Step S3. It can be seen from the experimental results that during the removal of PAA, increasing the temperature of the solution system can accelerate the carboxylation process and dissolution rate of PAA, achieving rapid dissolution of PAA.

[0163] Test Example 2

[0164] The following method was used to measure the optical properties and mechanical strength of the antireflection films in Application Examples 1-5, specifically as follows:

[0165] A spectrophotometer PE950 was used to test the light transmittance of the coated glass;

[0166] An ellipsometer was used to test the thickness and refractive index of the antireflection film;

[0167] According to the standard of GB / T 6739-2006, the pencil hardness of the antireflection film was tested;

[0168] The abrasion resistance of the antireflection film was tested according to the standard of JC / T 2170-2013.

[0169] Table 2: Optical properties and mechanical strength of the antireflection films in Application Examples 1-5

[0170]

[0171] Compared with the antireflection films prepared from the nanoparticles of Example 1 and Comparative Examples 1-3, the antireflection film prepared from the nanoparticles of Example 1 had the highest light transmittance, and its mechanical strength was also basically the same as that of the antireflection films in Comparative Examples 1-3. This is because the porosity of the nanoparticles in Comparative Examples 1-3 was low, resulting in a high refractive index of the antireflection film, which had a large gap from the refractive index index of the optimal film system design (the optimal refractive index is 1.23). However, due to the coating on the surface of the nanoparticles, the antireflection film prepared from the nanoparticles of Example 1 still had high mechanical strength.

[0172] Compared with the antireflection film prepared from the nanoparticles of Example 1 and Comparative Example 4, the optical properties are basically the same. Although the porosity of the multilayer silica nanoparticles in Example 1 decreases after coating, the particle size increases correspondingly, and the stacking gap between the particles increases accordingly, compensating for a part of the porosity of the antireflection coating, so that the overall optical properties of the antireflection film are basically the same as those in Comparative Example 4. However, the mechanical strength of the antireflection film in Example 1 is significantly higher than that in Comparative Example 4. This is because the silica shell layer coated on the surface of the hollow-mesoporous silica nanoparticles in the antireflection film of Example 1 improves the mechanical strength of the nanoparticles. During the process of external force collision and friction, the particles are not easily collapsed and broken. In contrast, the hollow-mesoporous silica nanoparticles in Comparative Example 4 are not surface-coated, and the porous structure results in poor particle stability, making them easily broken under external force, thus causing a decrease in the mechanical strength of the antireflection film.

Claims

1. A multilayer silica nanoparticle, characterized in that: The multilayer silicon dioxide nanoparticles sequentially comprise a hollow core, a mesoporous silicon dioxide intermediate layer and a silicon dioxide coating layer from the inside to the outside, and the overall porosity of the multilayer silicon dioxide nanoparticles is 25-50%.

2. The multilayer silica nanoparticle according to claim 1, wherein The multilayer silica nanoparticles have one or more of the following characteristics: The particle size of the multilayer silica nanoparticles is 80-120 nm; The thickness of the silica coating layer of the multilayer silica nanoparticles is 5-8 nm; The thickness of the mesoporous silica middle layer of the multilayer silica nanoparticles is 20-35 nm; The diameter of the hollow core of the multilayer silica nanoparticle is 30-70 nm; The specific surface area of ​​the multilayer silicon dioxide nanoparticles before being coated with the silicon dioxide coating layer is 320-400 m 2 / g; The mesopore diameter of the multilayer silica nanoparticles before being coated with the silica coating layer is 10-20 nm; The multilayer silica nanoparticles have a porosity of 30-55% before being coated with the silica coating layer; The multilayer silica nanoparticles do not contain a mesoporous pore former and a hollow pore former.

3. The method for preparing multilayer silica nanoparticles according to claim 1 or 2, characterized in that: The preparation method comprises: dispersing hollow silica nanoparticles in a mixed solvent of an alcohol solvent and water, adjusting the pH value of the solution to 7-14, adding a silicon source, reacting, forming a silica coating layer on the surface of the hollow silica nanoparticles, and obtaining the multilayer silica nanoparticles; wherein the hollow silica nanoparticles comprise a hollow core and a mesoporous silica shell.

4. The preparation method according to claim 3, characterized in that: The preparation method has one or more of the following characteristics: The particle size of the hollow silica nanoparticles is 70nm-110nm; The diameter of the hollow core of the hollow silica nanoparticle is 30-70 nm; The thickness of the mesoporous silica shell of the hollow silica nanoparticles is 20-35 nm; The specific surface area of ​​the hollow silica nanoparticles is 320-400 m 2 / g; The mesopore diameter of the hollow silica nanoparticles is 10-20 nm; The porosity of the hollow silica nanoparticles is 30-55%; The alcohol solvent is selected from C1-C4 alcohols, preferably ethanol; The volume ratio of the alcohol solvent to water in the mixed solvent is (5-10):1; The silicon source is tetraethyl orthosilicate; The mass ratio of the silicon source to the hollow silica nanoparticles is 1:(0.3-1); The reaction temperature is 20-30°C; The reaction time is 5-8h; Use ammonia to adjust the solution pH to 7-14.

5. The preparation method according to claim 3, characterized in that: The preparation method of the hollow silica nanoparticles comprises: S1: dissolving a hollow pore-forming agent, a mesoporous pore-forming agent, an initiator and a silicon source in a solvent, and reacting at 5-10° C. to obtain a solution containing nanoparticles P0, wherein the nanoparticles P0 comprise a hollow pore-forming agent core and a silicon dioxide surface layer, wherein the silicon dioxide surface layer comprises mesoporous channels and the mesoporous pore-forming agent filled in the mesoporous channels; S2: removing the mesoporous pore former in the mesoporous channels of the nanoparticles P0 by a centrifugal water washing method to obtain nanoparticles P1; S3: Dispersing the nanoparticles P1 in water, adjusting the pH value of the solution to 1-1.5, stirring at 60-70° C., and removing the hollow pore-forming agent by centrifugal washing to obtain the hollow silica nanoparticles.

6. The preparation method according to claim 5, characterized in that: The preparation method has one or more of the following characteristics: In step S1, the hollow pore-forming agent is polyacrylic acid, and the relative molecular weight of polyacrylic acid is preferably 3000-5000; In step S1, the mesoporous pore-forming agent is hexadecyltrimethylammonium bromide and / or hexadecyltrimethylammonium chloride; In step S1, the initiator is aqueous ammonia; In step S1, the silicon source is tetraethyl orthosilicate; In step S1, the solvent is a mixture of an alcohol solvent and water, and the alcohol solvent is preferably a C1-C4 alcohol, and more preferably ethanol; In step S1, the particle size of the nanoparticle P0 is 70-110 nm; In step S1, the mass ratio of the hollow pore former, the mesoporous pore former and the silicon source is 1:(0.5-1.5):(15-40); In step S1, the reaction time is 5-8h; Step S1 includes the following steps: S1-1: Mix the hollow pore-forming agent, the initiator and water evenly, then add them into the alcohol solvent and stir evenly to obtain a first mixed solution; S1-1: dissolving a mesoporous pore former in water, and then adding the mesoporous pore former to the first mixed solution obtained in step S1-1 to obtain a second mixed solution; S1-3: Add the silicon source to the second mixed solution, and react at 5-10° C. to obtain the solution containing the nanoparticles P0.

7. The preparation method according to claim 5, characterized in that: In step S2, the water used for centrifugal washing is ice water at a temperature of 0-5°C; and / or In step S3, the stirring time is greater than or equal to 10 hours, preferably 10-12 hours.

8. Multilayer silicon dioxide nanoparticles prepared by the preparation method according to any one of claims 3 to 7.

9. An anti-reflection film comprising the multilayer silica nanoparticles according to claim 1, 2 or 8.

10. A solar cell comprising the anti-reflection film according to claim 9.

Citation Information

Patent Citations

  • A one-step method for preparing hollow mesoporous silica functional microspheres

    CN110217802B

  • Method for preparing hollow mesoporous silica by using polyethyleneimine as structure-directing agent and hollow mesoporous silica

    CN117585681A

  • Method for preparing cellulose supported hollow SiO2 microsphere catalytic carrier

    CN106629745A

  • Anti-reflection anti-dazzle coated glass

    CN114716153A

  • Hollow silicon dioxide microsphere with double-layer shell structure and preparation method of hollow silicon dioxide microsphere

    CN119240719A